The effectiveness of typeface on masthead design: Malay horror movie poster / Syahrul Nizam Shaari ... [et al.] - Shaari, Syahrul Nizam; Mohd Nazri, Nur Ilyana Syuhada; Abdul Kadir, Norita; Ramlie, Mohd Khairulnizam (Universiti Teknologi MARA, Perak, 2024)
A well-designed typeface will have qualities that are consistent throughout the masthead design. We have been revealed with many film posters in this world. Despite a century of horror film production and entertainment, little study has looked at why people watch horror films and how it affects their behaviour, memory, and emotions. The paper considers a typeface usage on masthead design for Malay horror movie posters as one of the main keys for a good quality of horror movie posters. There are various of Malaysian horror movie posters that failed to visualize the elements to draw the emotions of the audience. Most of the failed element usage are typography usage. One of the reasons the issues arose was that our designers lacked understanding of the significance of using typography itself. Therefore, the main key for this research is to study the effectiveness and significances of typeface usage on masthead design for Malaysian movie posters. This paper will discuss on the elements of the masthead design which is Typography usage on Malaysian horror movie posters.